2020
DOI: 10.1183/23120541.00368-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising community networks for early identification of tuberculosis and treatment initiation in Cambodia: an evaluation of a seed-and-recruit model

Abstract: Background and objectivesThe effects of active case finding (ACF) models that mobilise community networks for early identification and treatment of tuberculosis (TB) remain unknown. We investigated and compared the effect of community-based ACF using a seed-and-recruit model with one-off roving ACF and passive case finding (PCF) on the time to treatment initiation and identification of bacteriologically confirmed TB.MethodsIn this retrospective cohort study conducted in 12 operational districts in Cambodia, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Our analyses revealed a substantial delay between the onset of TB symptoms and TB care-seeking among high burden countries, highlighting the need to continue to shape knowledge, change attitude, and raise awareness of the community, people at risk of TB, and the health providers. Specific vulnerabilities such as sex disparities in care-seeking, being older, and geographic isolation should be recognized and addressed through tailored approaches to improve access to TB services and early diagnosis [ 184 ]. It is also crucial to improve the consciousness of the society regarding TB to battle stigma, and networks [ 185 ] of support from within the families, the grassroots, and institutions could create an enabling environment for early care-seeking and treatment adherence and success.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses revealed a substantial delay between the onset of TB symptoms and TB care-seeking among high burden countries, highlighting the need to continue to shape knowledge, change attitude, and raise awareness of the community, people at risk of TB, and the health providers. Specific vulnerabilities such as sex disparities in care-seeking, being older, and geographic isolation should be recognized and addressed through tailored approaches to improve access to TB services and early diagnosis [ 184 ]. It is also crucial to improve the consciousness of the society regarding TB to battle stigma, and networks [ 185 ] of support from within the families, the grassroots, and institutions could create an enabling environment for early care-seeking and treatment adherence and success.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study did not evaluate the effect of C-DOTS on TB stigma, it reinforced the notion of community mobilization and support in TB care. A separate study on the same population has empirically shown that a TB case-finding strategy that mobilizes the community to find and refer people presumptive of TB living in the same community has led to early identification of TB and treatment initiation [ 14 ]. Therefore, it is vital to continue recognizing the roles of the people affected by TB and rally community-driven approaches in monitoring and combatting stigma and ending TB.…”
Section: Discussionmentioning
confidence: 99%
“…For the IDIs, we purposively selected participants from the same cohort based upon maximum variation on these criteria—care-seeking behavior (short delay/long delay to TB diagnosis), sex (men/women), and residence (urban/rural). The details of the study population and TB diagnostic criteria have been described elsewhere [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our analyses revealed a substantial delay between the onset of TB symptoms and TB care-seeking among high burden countries, highlighting the need to continue to shape knowledge, change attitude, and raise awareness of the community, people at risk of TB, and the health providers. To improve access to TB services and early diagnosis, specific vulnerabilities such as sex disparities in careseeking, being older, and geographic isolation should be recognized and addressed through tailored approaches [180] It is also crucial to improve consciousness of the society regarding TB to battle stigma, and networks [181] of support from within the families, the grassroots, and institutions could create an enabling environment for early care-seeking, treatment adherence and success. In contrast to patient delay, the shorter health system and treatment delay were encouraging.…”
Section: Discussionmentioning
confidence: 99%